Memorandum re Shortage of Nurses - Labour Party (Great Britain). National Executive Committee ; Labour Party (Great Britain). Advisory Committee on Public Health ; Joint Research Dept. of the Trades Union Congress and the Labour Party; MacCallum, Maude
1924-07 1924 1920s 8 pages - 7 - (92) her old age. Judging by the nurses of forty and upwards who are trying to find work, there is in a number of cases only the workhouse infirmary for them in the end. Under these circumstances, and they are pretty generally known, is it likely that parents would be willing to send their daughters, or that intelligent girls would be willing to go, into hospitals to be treated as serfs while there, and to earn a precarious living after they leave, sometines with impaired health due to overwork? We are of the opinion that a probationer in hospital should receive, if any, a very small salary during her period of training. We understand that in other trades and professions it is the custom to give apprentices or pupils a small remuneration, and it should be remembered that not only are nurses supposed to be learning their business, but that no hospital could exist for a week without their services, so that a small remuneration for services rendered would not be out of place. We are of the opinion, however, that as soon as she has fulfilled her contract and received her certificate as a trained nurse, a minimum salary should be fixed, say £100 per annum. Very few well paid posts are given to nurses, the "plums" going to the friends of matrons, medical men, etc., as was proved lately when an examination officer was required by the General Nursing Council for England and Wales. In this case the nominee of a medical man; age about 24, no experience of nursing, hardly knowing one kind of hospital from another, was given the post of examination officer at £400 a year, when many ex-matrons and nurses, fully qualified to carry out the duties involved, were put aside. We maintain that a medical man ought not to have interfered in this matter. It is an insult to suppose that not one nurse in the whole 292/842/1/14